Synergistic curative effects of Trichoderma hamatum and Rumex dentatus against Alternaria alternata, the causal agent of tomato leaf spot disease - Philip, Bassant; Eid, Asia R.; Bayoumi, Shokry R.; Heflish, Ahmed; Atallah, Osama O.; Abdelwahab, Eman A.; Michalecka, Monika; Behiry, Said I.; Abdelkhalek, Ahmed; Al-Askar, Abdulaziz A. (Frontiers in Plant Science, 2025)
The current investigation identified and characterized Alternaria alternata as the causal agent of tomato leaf spot through morphological traits and multilocus phylogenetic analysis [internal transcribed spacer (ITS), translation elongation factor 1-alpha (tef1-α), and the RNA polymerase II second-largest subunit (RPB2)], thereby confirming its classification within the A. alternata complex. Four Trichoderma isolates (Ham34, Ham35, Ham36, and Ham37) were recovered from loamy rhizosphere soil associated with healthy tomato plants. Among them, Ham34 (Trichoderma hamatum) showed the most significant antagonistic activity in dual-culture assays. Ethyl acetate extracts of all isolates exhibited concentration-dependent antifungal effects, with Ham34 showing the most potent inhibition (57.8% at 2000 µg/mL). Gas chromatography-mass spectrometry (GC-MS) profiling of the Ham34 extract identified bioactive metabolites, including (-)-spathulenol (28.2%) and glycerol 1,2-diacetate (21.4%). Among the four tested plant extracts, Rumex dentatus (RD) showed superior activity, achieving 68.5% inhibition at 2000 µg/mL, followed by moderate inhibition from Cichorium intybus, Conium maculatum, and Capsicum annuum. High-performance liquid chromatography (HPLC) profiling of Rumex dentatus extract revealed high levels of phenolic and flavonoid compounds, with a total concentration of 108.63 µg/mL. The primary identified constituents were rutin (33.1 µg/mL), gallic acid (22.7 µg/mL), and chlorogenic acid (17.9 µg/mL). Under greenhouse conditions, tomato plants (Solanum lycopersicum cv. Super Strain B) were treated with Ham34 ethyl acetate extract, RD extract, and their combination (Ham34 + RD). The combined treatment significantly reduced disease incidence (11.1%) and severity (16.7%), outperforming Ridomil Gold® in disease suppression. Growth parameters and chlorophyll content (SPAD) were significantly enhanced in the combined treatment, with increased shoot and root biomass and length. Biochemical analyses revealed that the combined Ham34 + RD treatment enhanced antioxidant enzyme activities, including catalase (CAT) and peroxidase (POD), and increased total soluble protein content to 342.8 µg/mL compared to 331.1 µg/mL in the untreated control. Moreover, the treatment elevated total phenolic content to 256 mg GAE/g, indicating improved stress mitigation and enhanced plant vigor. This eco-friendly approach provides a low-cost, chemically stable, and safe alternative to synthetic fungicides, highlighting the synergistic potential of integrating R. dentatus and T. hamatum for sustainable management of A. alternata-induced tomato leaf spot.